1995
DOI: 10.1021/bi00005a001
|View full text |Cite
|
Sign up to set email alerts
|

Complete Restoration of Activity to Inactive Mutants of Escherichia coli Thymidylate Synthase: Evidence that E. coli Thymidylate Synthase is a Half-the-Sites Activity Enzyme

Abstract: Escherichia coli thymidylate synthase (TS) is a dimeric protein containing identical subunits. When R126E, an inactive mutant of this enzyme, was incubated at room temperature with other inactive mutants of E. coli, TS enzyme activity gradually reappeared. The rate of activity restoration was dependent on the mutant employed. In the case of C146W, an active site mutant, the half-time required for maximal activity restoration was about one hour, which was about 500-fold faster than that obtained with C146S. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 21 publications
7
82
0
Order By: Relevance
“…These results imply that the K282E/R283E TS-dead mutant is unable to form the covalent dUMP⅐CH 2 H 4 -folate⅐enzyme complex requisite properly for chemistry to take place. Restoration of Activity to Assess Global Stability-From studies in E. coli, it is known that TS, which exists as a dimer in most species, exhibits half-the-sites activity, meaning that at any given time, only one half of the TS dimer is kinetically competent (31,32). In E. coli TS it was shown that the amino acid Arg-126 participates in the catalytic site of the opposite half of the dimer and that a TS dimer in which both Arg-126 residues have been mutated to glutamic acid is TS-dead.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results imply that the K282E/R283E TS-dead mutant is unable to form the covalent dUMP⅐CH 2 H 4 -folate⅐enzyme complex requisite properly for chemistry to take place. Restoration of Activity to Assess Global Stability-From studies in E. coli, it is known that TS, which exists as a dimer in most species, exhibits half-the-sites activity, meaning that at any given time, only one half of the TS dimer is kinetically competent (31,32). In E. coli TS it was shown that the amino acid Arg-126 participates in the catalytic site of the opposite half of the dimer and that a TS dimer in which both Arg-126 residues have been mutated to glutamic acid is TS-dead.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, one TS-dead mutant whose activity can be restored by heterodimerization is K48E, homologous to K282E in L. major (31). We hypothesized that if Lys-282 and Arg-283 were crucial to global stability of the protein, then dissociating the TS dimer and reassociating the K282E/R283E mutant with an active site mutant may not lead to restoration of TS activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The forward commitment C f is described by equation 7: [7] where [B] is the concentration of the second substrate (CH 2 H 4 folate in this case). As apparent from Eq 6 and Eq 7, the observed T (V/K) is dependent on the concentration of B and its observed value can change between two finite values (C f changes from k 9 /k 5 to k 9 /(k 5 + k 4 ) as [B] changes from infinity to zero).…”
Section: Proton Abstractionmentioning
confidence: 99%
“…Kevin McDonagh and Philip Stetson (University of Michigan). For pLNCX.eTS, the eTS gene was amplified by polymerase chain reaction using pBTAH 18 as a template as well as primers that added EcoRI and XhoI sites to the 5Ј end of the gene and EcoRI and ClaI sites to the 3Ј end of the gene. The modified eTS fragment was then ligated into pUC18 (Life Technologies) at the EcoRI cloning site.…”
Section: Retroviral Constructsmentioning
confidence: 99%